2019
DOI: 10.1029/2018jd029796
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution, Multilayer Modeling of Singapore's Urban Climate Incorporating Local Climate Zones

Abstract: We applied Weather Research and Forecasting (WRF) model's Multilayer Urban Canopy Model (MLUCM) to simulate the urban climate of Singapore during a hot period in April 2016. The high‐resolution local climate zone (LCZ) map was used as urban land use/land cover data in order to study the intraurban variability in different LCZ classes. The LCZ map for Singapore was developed by adopting the World Urban Database and Access Portal Tools (WUDAPT) methodology based on satellite remote sensing imageries and building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 81 publications
6
56
1
Order By: Relevance
“…This work used commercial satellite optical imagery to generate a 3-D model of urban form and vegetation across the entire city of Singapore, providing the data source to run radiative transfer simulations and modeling tasks at any desired location in the city. Such data has also been used in recent work on wind flow simulation and on a study of the urban climate of Singapore [34,35]. The accuracy of deriving tree height from satellite optical data remains low (3.5 m in this case).…”
Section: Discussionmentioning
confidence: 99%
“…This work used commercial satellite optical imagery to generate a 3-D model of urban form and vegetation across the entire city of Singapore, providing the data source to run radiative transfer simulations and modeling tasks at any desired location in the city. Such data has also been used in recent work on wind flow simulation and on a study of the urban climate of Singapore [34,35]. The accuracy of deriving tree height from satellite optical data remains low (3.5 m in this case).…”
Section: Discussionmentioning
confidence: 99%
“…The commenter misquoted Mughal et al (2019) that it was the first time the model was applied in a tropical city. Mughal et al (2019) clearly stated that there are other studies (Liao et al, 2014;Valdés, 2018;Wang et al, 2017) in the tropics which have utilized WRF/MLUCM.…”
Section: We Studied a Special Month With No Energy Balance Data Availmentioning
confidence: 99%
“…Vegetation covers 56% of the total land area (Yee et al, 2011). The evapotranspiration's cooling effect and shade provided by trees have been widely investigated in Singapore, even by some coauthors of Mughal et al (2019), who have concluded that trees cannot be ignored to assess the local climate (Dissegna et al, 2019; Liu et al, 2017). However, in this study, Mughal et al did not consider the presence of trees.…”
Section: What About Evapotranspiration and Tree Shade?mentioning
confidence: 99%
“…In this context, the article of Mughal et al (2019) is a good example of how not to validate the performance of an urban climate model and how simplistic assumptions and wrong interpretations aiming to avoid the design of a holistic experiment do not help to understand the urban thermal climate.…”
Section: Introductionmentioning
confidence: 99%